A Hybrid IFRS–GRI Measurement Model for Assessing Public-Sector Sustainability Reporting in Asian Governments - Dian Anita Nuswantara; Lintang Venusita; Ika Permatasari; Hariyati; Rida Perwita Sari (Environment and Social Psychology, 2026)
This study develops a hybrid measurement framework to assess the consistency and depth of sustainability reports published by governments in four Asian countries: Indonesia, Malaysia, Singapore, and Hong Kong. Although global reporting standards are increasingly developing, reporting practices in the region remain diverse, the indicators used are not yet uniform, and no evaluation tools are available that can reliably produce cross-country comparisons. To bridge this gap, this study integrates IFRS S1 and S2 with GRI Standards to develop the Public Sector Sustainability Disclosure Index (PSSDI). Using a phased qualitative design, this study developed an index comprising four pillars and 32 sub-indicators. The findings show significant differences in maturity levels, institutional capacity, and the quality of information disclosed. Singapore and Hong Kong are at the most advanced level, Malaysia is at an intermediate stage, while Indonesia is still in the early phase. These results provide an empirical basis for promoting harmonization of reporting at the regional level and identifying institutional and technical barriers that hinder cross-country comparability. The study offers an analytical model for governments to strengthen national reporting systems, improve transparency, and support more targeted policy decisions on climate issues.